Periodization and programming in sports - Fisher, J. P.; Csapo, R. (Sports, 2021)
Periodization is a generally accepted approach to manage athletic performance by the sub-division of training programs into sequential, specifically focused training periods. Periodization implements structured variability into the training process, with the aim of maximizing performance in the most critical phases of the competitive season and/or improving long-term development. A recent review specifically compared periodized and non-periodized resistance training practices for strength and hypertrophy adaptations [1]. This prompted a series of responses considering the SAID principle (specific adaptations to imposed demands) and the use of heavier-loads close to testing time-points [2], and, often overlooked, confounding variables which appear to impact strength and hypertrophy adaptations (e.g., exercise selection, supervision, etc.) [3].